The Legal Certainty in Gambling Criminal Acts in the Palembang District Court Decision Number: 86/PID.B/2024/PN PLG - Effendi, Effendi; Yusi, Suryani; Fitri, Aidil (JURNAL HUKUM SEHASEN, 2025)
The crime of gambling can not only be carried out in general (conventional) but with the rapid development of technology and information, gambling can also be done online. Gambling that is carried out in general (conventional) already has an article that regulates it, namely Article 303 of the Criminal Code, which is less effective if applied to online gambling. Therefore, in the crime of online gambling, there is already a specific article that regulates it, namely Article 27 paragraph (2) of the ITE Law. If there is a crime of online gambling but is charged with Article 303 of the Criminal Code, there needs to be relevant legal certainty. Where online gambling already has a regulation that regulates it specifically, namely Article 27 paragraph (2) of the ITE Law. As in criminal law, namely the principle of lex specialis derogate legi generalis, where if there is a rule that is specific, it will override the rule that is general.